Testing the Acceptance of Soybean Tempeh Substituted with Chicken Liver Flour to Prevent Iron Deficiency Anemia - Ma'arif, Mohammad Zainul; Yuniars Renowening; Himmatunnisak Mahmudah (Sean Institute, 2023)
Iron deficiency anemia is a major health problem caused by iron deficiency. Many women of childbearing age and adolescents in Indonesia experience this condition. This condition needs to be handled appropriately because it can have a negative impact on the quality of life of teenagers and their offspring. Therefore it is necessary to develop food products with high iron content to increase the dietary iron intake. Soybean tempeh is a local food that can be developed as a food source for iron by substituting chicken liver flours. Chicken liver is a food source of high-quality animal protein and heme iron. This study aimed of this research was to analyze the acceptability of soybean tempeh products substituted with chicken liver flour. This study used a completely randomized experimental design. There were 4 formulas and 1 control group without substitution. Percentage of chicken liver flour substitution in groups F1 (5% chicken liver flour), F2 (10% chicken liver flour), F3 (15% chicken liver flour), and F4 (20% chicken liver flour). Acceptability tests were performed on the color, aroma, taste, and texture parameters using 25 semi-trained panelists. The acceptability test results showed that F1 underwent the closest acceptability test to the control group, especially in terms of color, taste, and texture (p>0,05). The F2, F3, and F4 groups were less preferred, especially in terms of aroma and taste parameters. As a product intended to meet dietary iron requirements, efforts need to be made to improve the acceptability of aroma parameters.